Functional Group of Spiders in Cultivated Landscape Dominated by Paddy Fields in West Java, Indonesia - I WAYAN SUANA; DEDY DURYADI SOLIHIN; DAMAYANTI BUCHORI; SJAFRIDA MANUWOTO; HERMANU TRIWIDODO; CHRISTIAN HANSJOACHIM SCHULZE (HAYATI Journal of Biosciences, 2009)
Distribution of spiders in all colonized environments is limited by biotic and abiotic factors requiring adaptations with respect to, for example microhabitat choice and hunting behavior. These two factors were frequently used to group spiders into functional groups. In this study our objectives were to (i) group of genera of spiders into functional group based on their microhabitat specificity, hunting behavior, and daily activity; and (ii) compare the number and composition of functional group of spider at each habitat type and period of paddy growth. The study was conducted at a landscape dominated by paddy fields in Cianjur Watershed for a period of 9 months. Four different habitat types (paddy, vegetable, non-crop, and mixed garden), were sampled using five trapping techniques (pitfall traps, farmcop suction, sweep netting, yellow-pan traps, and sticky traps). The Unweighted Pair-Group Average and the Euclidean Distances were used to generate dendrogram of functional group of spider. We found 14 functional groups of spider at genus level. The number of functional group of spider at four habitat types was differing, but the composition was similar, because all habitats were closed to each other. Habitat structure diversity and disturbance level influenced the number of functional group of spider. Different architecture of vegetation and availability of differ prey during paddy growth, causing the composition of functional group of spider in each period of paddy growth was changed, although its number was unchanged. Key words: spiders, functional group, agricultural landscape, Cianjur Watershed